The accuracy of neck circumference for assessing overweight and obesity: a systematic review and meta-analysis. (17th November 2017) - Kroll, Caroline; Mastroeni, Silmara S. B. S.; Czarnobay, Sandra A.; Ekwaru, John Paul; Veugelers, Paul J.; Mastroeni, Marco F.
Abstract: Context: Neck circumference (NC) has been suggested as an alternative measure to screen for excess body weight. Objective: The aim of this study was to demonstrate the accuracy of neck circumference (NC) as a measure for assessing overweight and obesity in both sexes in different age groups. Methods: Detailed individual search strategies were developed for each of the following bibliographic databases: Cochrane, LILACS, PubMed/MEDLINE, Science Direct, Scopus and Web of Science. The QUADAS-2 checklist was used to assess the methodology of the studies included. Results: Thirty-eight assessments were performed in 11 articles according to age, sex and weight status. Using sensitivity and specificity, 27 assessments (71.0%) considered NC an accurate measure to diagnose overweight and obesity. The best sensitivity and specificity were found for the age >19 years (82.0%, 82.0%), female (80.0%, 73.0%), and obese (80.0%, 85.0%) categories. Conclusion: NC is an accurate tool for assessing overweight and obesity in males and females of different age groups and could be used to screen for excess body weight in routine medical practice or epidemiological studies. It is also believed that more studies will permit the creation of a reference dataset of NC cut-off values for world populations.